The role of hippocampal theta oscillations in working memory impairment in multiple sclerosis. Issue 5 (28th November 2020) - Costers, Lars; Van Schependom, Jeroen; Laton, Jorne; Baijot, Johan; Sjøgård, Martin; Wens, Vincent; De Tiège, Xavier; Goldman, Serge; D'Haeseleer, Miguel; D'hooghe, Marie Beatrice; Woolrich, Mark; Nagels, Guy
Abstract: Working memory (WM) problems are frequently present in people with multiple sclerosis (MS). Even though hippocampal damage has been repeatedly shown to play an important role, the underlying neurophysiological mechanisms remain unclear. This study aimed to investigate the neurophysiological underpinnings of WM impairment in MS using magnetoencephalography (MEG) data from a visual‐verbal 2‐back task. We analysed MEG recordings of 79 MS patients and 38 healthy subjects through event‐related fields and theta (4–8 Hz) and alpha (8–13 Hz) oscillatory processes. Data was source reconstructed and parcellated based on previous findings in the healthy subject sample. MS patients showed a smaller maximum theta power increase in the right hippocampus between 0 and 400 ms than healthy subjects ( p = .014). This theta power increase value correlated negatively with reaction time on the task in MS ( r = −.32, p = .029). Evidence was provided that this relationship could not be explained by a 'common cause' confounding relationship with MS‐related neuronal damage. This study provides the first neurophysiological evidence of the influence of hippocampal dysfunction on WM performance in MS. Abstract : This study is the first to provide neurophysiological evidence of impaired hippocampal WM processing in MS that can be related to WM performance. Our data suggests that impaired theta oscillatory processes in the right hippocampus, supposedly underlying WM encoding, lead to slower reaction times on the task. We also provide evidence that this relationship cannot be accounted for by general MS‐related neural damage (specifically hippocampal and white matter damage).